Annual Plan 1988-89 Orissa - Planning Commission (Planning Commission, 1987)
However, compared to the achievements at the national level, the performance of the State in the power and industrial sectors has been poor. It would be seen from the data (for 1980—86) given below that while the growth in the production of foodgrains has been good, the achievement in power generation and industrial income has not been good enough. Cumulatively, these have brought down the growth of the State Income. It is, therefore, necessary improve upon the growth rate of industries and power during the Seventh Plan for an over all improvement of the State economy.
Government of Orissa Planning and Co-ordination Department